Neutron diffraction residual stress mapping in same gauge and differential gauge tailor-welded blanks - Clapham, Lynann; Abdullah, Kassim Abdulrahman; Jeswiet, J J; Wild, P M; Rogge, R (Elsevier, 2004)
Neutron diffraction has been used to determine the residual stresses in the weld region of laser-welded tailor-welded blank (TWB) samples. Residual stresses in same gauge and differential gauge TWB samples are examined in the as-welded condition as well as after uniaxial loading to 0.5, 3.0 and 7.0% strain. Results indicate that stress distributions can be quite complex, particularly following deformation. Overall, however, two major conclusions were drawn: first, residual stresses around laser welds in these TWBs tend to be small compared with stresses reported for conventional welding processes. Secondly, inmost cases the peak residual stresses tend to remain the same or diminish with subsequent deformation.